Integralistik Indonesia Dan Tantangan Identitas Nasional Dalam Dialog Dengan Pemikiran Rousseau - Thomas Dwiki; Armada Riyanto (Universitas Negeri Semarang, 2026)
The concept of the integralistic state in Indonesia emerged as an effort to decolonize the political system that once separated individuals from the state. Jean-Jacques Rousseau’s notion of the general will likewise emphasizes the essential unity between the state and society in pursuing the common good. This study aims to analyze and compare the Indonesian concept of an integralistic state with Rousseau’s perspective on the general will through a literature-based and philosophical approach. The findings indicate that both frameworks seek to establish harmony between society and the state, yet they differ philosophically. The Indonesian concept is rooted in the communal values of gotong royong and Pancasila, whereas Rousseau’s thought is grounded in individualism directed toward the common interest. The contribution of this study lies in enriching philosophical discourse on the state and society relationship, offering insights relevant to strengthening Indonesia’s national identity in the contemporary era.